Be karmavīra bhāīo : Śrī Kuṃvarajībhāī ane Śrī Kalyāṇajībhāī - Desai, Ishwarlal Ichharam, 1903- (Vallabha Sevāmaṇḍaḷa, 1974)
Biographies of Kuṃvarajībhāī Viṭhṭhalajībhāī Mahetā, b. 1886 and Kalyāṇajī Viṭhṭhalabhāī Mahetā, 1890-1973, social and political activists of Gujarat.